Abiotic and biotic responses to woody debris additions in restored old fields in a multi‐site Before‐After‐Control‐Impact experiment. Issue 7 (4th July 2022) - Parkhurst, Tina; Prober, Suzanne M.; Farrell, Mark; Standish, Rachel J.
Abstract: Ecological restoration of former agricultural land can improve soil conditions, recover native vegetation, and provide fauna habitat. However, restoration benefits are often associated with time lags, as many attributes, such as leaf litter and coarse woody debris, need time to accumulate. Here, we experimentally tested whether adding mulch and logs to restoration sites in semi‐arid Western Australia can accelerate restoration benefits. All sites had been cropped and then planted with native trees and shrubs (i.e., Eucalyptus, Melaleuca, and Acacia spp.) 10 years prior to our experiment, to re‐establish the original temperate eucalypt woodland vegetation community. We used a Multi‐site Before‐After‐Control‐Impact (MBACI) design to test the effects on 30 abiotic and biotic response variables over a period of 2 years. Of the 30 response variables, a significant effect was found for just four variables: volumetric water content, decomposition, native herbaceous species cover and species richness of disturbance specialist ants. Mulch addition had a positive effect on soil moisture when compared to controls but suppressed growth of native (but not exotic) herbaceous plants. On plots with log additions, decomposition rates decreased, and species richness of disturbance specialist ants increased. However, we found no effect on total species richness and abundance of other ant species groups. The benefit of mulch to soil moisture was offset by its disbenefit to native herbs in our study. Given time, logs may also provide habitat for ant species that prefer concealed habitats. Indeed, benefits to other soil biophysical properties, vegetation, and ant fauna may require longer time frames to be detected. Further research is needed to determine whether the type, quantity, and context of mulch and log additions may improve their utility for old field restoration and whether effects on native herbs are correlated with idiosyncratic climatic conditions. Abstract : Benefits of ecological restoration are often associated with time lags, as many attributes, such as leaf litter and coarse woody debris, need time to accumulate, particularly in arid ecosystems. Here we used a 2 year MBACI experiment to test if adding woody debris to restored eucalypt woodlands in semi‐arid western Australia can accelerate restoration outcomes. We found that only few abiotic and biotic variables responded positively, and conclude that detectable benefits of additional restoration actions may be slow in arid ecosystems.